Pengaruh Komposisi Kertas Bekas Terhadap Sifat Mekanik dan Ketahanan Air pada Komposit (Kertas Bekas, Gipsum dan PVA) - Muntazar Muntazar; Samsul Rizal; Sulaiman Thalib (Jurnal Teknik Mesin Unsyiah, 2016)
The purpose of this study was to determine the effect of used paper composition on the mechanical properties and water resistance to the composite (used-paper, gypsum and PVA) expected a composite that has good flexural strength, good water resistance and has a lighter weight than current composites. The materials used in the test specimens are used paper, gypsum and PVA. This research was conducted at the Laboratory of Mechanical Engineering Materials Syiah Kuala University, the flexural testing using ASTM C473 to get the mechanical properties, a standard SNI 03-6434-2000 used to test the water resistance and methods of morphology (SEM photo) to study the structure of the composite. The results showed that 20 percent composites by the addition of filler material (used paper, PVA) to get flexural the value of 9,00 MPa, water resistance of 4,067 percent and have a good bond, mutual binding between the gypsum crystals with used paper fibers. The of all testing, composites with 20 percent adding filler material have lower weight get of 8.98 percent when compared with that sold products.